Mối quan hệ giữa hành vi khiếm nhã và sự kiệt sức trong học tập của sinh viên Việt Nam - Nguyễn Tường Trâm, Anh; Nguyễn Vân, Anh; Nguyễn Thúy Lan, Anh; Phạm, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Incivility is one of the leading causes affecting the psychology of students. It causes negative effects affecting academic performance. Therefore, the study aims to examine the impact of incivility behavior on students’ academic burnout through affective events theory. In addition, the study also uses conservation of resources theory to explain the role of forgiveness in the relationship between incivility and academic burnout. The conceptual model is tested based on 265 student observations collected from June to July 2023. The results confirmed that incivility had a negative impact on students and thereby caused academic burnout. An interesting finding of the research is that forgiveness is a positive factor in weakening the influence of incivility on emotions and motivations. This study also proposes related implications and solutions.